Incidence of Nitrate Toxicity in Buffalos in Andhra Pradesh - T. Mohanamba; M.Vasundhara Priyanka; L. Ratna Kumari; R.Amarendra Kumar (The Indian Veterinary Journal, 2024)
Nitrate poisoning occurs in animals due to consumption of fodder or drinking water containing high nitrate levels. Incidence of nitrate poisoning occurred in 20 buffalos of Santhanuthalapadu village of Prakasam dist. Affected animals exhibited symptoms like respiratory distress, cyanotic to brownish discolouration of mucous membranes and death in some cases. Ailing animals recovered following treatment with 1% solution methylene blue. The qualitative test for nitrate in water samples and fodder samples was done with Sulphanilic acid and diphenylamine reagent. Quantification was done by AOAC methods. The farmers were advised to give nitrate free water to the animals and to get the water samples often tested for nitrates.